Electromagnetic finite element design of axial flux permanent magnet machines for low speed applications - Ferreira, Ângela P. (2014)
© 2014 IEEE. The higher torque to volume ratio of Axial Flux Permanent Magnet (AFPM) machines, when compared with their radial flux counterparts, is enhanced in multi pole design, making them suitable for low speed applications. This paper presents a comprehensive approach to the finite element-aided electromagnetic design of a double-sided AFPM machine with internal rotor. The Finite Element (FE) model is included in a coupled electromagnetic-thermal design procedure. Special attention is given to leakage fluxes, synchronous and armature reaction inductances and no-load electromotive force computation. The evaluation of the FE model routine of the design procedure is performed through experimental validation of a prototype machine.